Pyelonephritis in Pregnancy: Prediction of Prolonged Hospitalization and Maternal Morbidity using Prognostic Scoring Systems - Valent, Amy M.; Peticca, Katie; DiMatteo, Alexandra; Banks, Shimeka; Shah, Ronak; Chernicky, Lindsey; Weitz, Beth; Armistead, Casey; Hill, James; Towers, Craig; Lewis, David; Magann, Everett F.; Chauhan, Suneet P.; Hook, James W. Van (American Journal of Perinatology, 2017)
Objective This study aims to evaluate the usefulness of prognostic scoring systems to differentiate women admitted for pyelonephritis who develop maternal morbidity and require prolonged hospitalization.Study Design Multicenter retrospective cohort study to compare the Acute Physiology and Chronic Health Evaluation II (APACHE II) and Modified Obstetric Early Warning System (MOEWS) to predict prolonged hospitalization (> 4 days) and composite maternal morbidity for all pregnant women admitted with pyelonephritis between 2012 to 2013. One-way analysis of variance for continuous variables, Fisher's exact test for categorical variables, and receiver operating characteristic curves were used.Results Among 123 pyelonephritis cases analyzed, 25 (20%) required prolonged hospitalization. Women with prolonged hospitalization had higher rates of composite maternal morbidity, required diagnostic imaging, and had delayed administration of intravenous antibiotics (292 ± 381 vs. 218 ± 233 min, p = 0.002). APACHE II and MOEWS scores calculated from data collected within the first 24 hours of admission had a modest ability to discriminate maternal morbidity (APACHE II: area under the curve [AUC], 0.72; 95% confidence interval [CI], 0.58–0.86 and MOEWS: AUC, 0.71; 95% CI, 0.56–0.85).Conclusion We observed that one in five pregnancies admitted for treatment of pyelonephritis requires hospitalization for over 4 days with significant maternal morbidities. Prognostic scoring systems may be useful clinical tools to assess these patients systematically and improve morbidity.
Keywords: pyelonephritis; prognostic scoring systems; morbidity; prolonged hospitalization; pregnancy